Il tempo e l’aspetto nel discorso. Italiano e olandese a confronto - Meroni, Luisa; van Spijk, Yoïn; Pinto, Manuela (Incontri. Rivista europea di studi italiani, 2017)
Time and aspect in speech. Italian and Dutch in comparison The Italian and Dutch verbal systems differ not only in the richness of the forms exhibited by Italian, but also in the way in which aspect is realized in the two languages. Despite a number of similarities, the Italian past tense is potentially problematic for a Dutch speaker from both an aspectual and a pragmatic point of view. The present study aims to highlight a possible differentiating factor on the use of past tenses in the two languages. In particular we follow Boogart (1999), who studied the verbal system of Dutch and English, and propose that while the ‘discursive mode’ (i.e. the speaker’s intentions) is relevant in determing the choice between different past tenses in Dutch, it is irrelevant when the same choice has to be made in Italian. In order to evaluate this hypothesis we report the results of a study conducted with monolingual speakers of Dutch and Italian. The results show that while the ‘discursive mode’ is crucial in Dutch, Italian responds solely to aspectuality. Furthermore, our data suggest that aspect is in Dutch mainly a pragmatic phenomenon. In highlighting a clear difference between the two languages, our study consitutes an important contribution to the study of cross linguistic interference in learning a second language, since it explains the nature and direction of linguistic interference in Dutch native speakers (L1) learning Italian (L2).